Such a clever girl : a novel - Kane, Darby (William Morrow, 2026)
Fifteen years ago, the Tanner family vanished without a trace. As rumors fade into local folklore, the mystery of their disappearance seems destined to remain unsolved, until Aubrey Tanner returns as a hardened thirty-year-old with secrets etched in her silence. As the past resurfaces, old alliances fray. A teacher, a café owner, and a psychologist are drawn together by memories they'd rather forget. With tension rising and danger lurking, one thing is clear: someone is destined to kill again.